2001
DOI: 10.1038/88497
|View full text |Cite
|
Sign up to set email alerts
|

The dissociation of color from form and function knowledge

Abstract: We report on two brain-damaged subjects who exhibit the uncommon pattern of loss of object color knowledge, but spared color perception and naming. The subject P.C.O., as in previously reported patients, is also impaired in processing other perceptual and functional properties of objects. I.O.C., in contrast, is the first subject on record to have impaired object color knowledge, but spared knowledge of object form, size and function. This pattern of performance is consistent with the view that semantic inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
123
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(133 citation statements)
references
References 29 publications
9
123
1
Order By: Relevance
“…Indeed, it is unlikely given the neuropsychological evidence for a double dissociation in performance on the two tasks (Luzzatti & Davidoff. 1994;Miceli et al, 2001;Davidoff & Roberson, 2004). …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it is unlikely given the neuropsychological evidence for a double dissociation in performance on the two tasks (Luzzatti & Davidoff. 1994;Miceli et al, 2001;Davidoff & Roberson, 2004). …”
Section: Discussionmentioning
confidence: 99%
“…Our stored knowledge of the concept banana evidently includes knowledge of physical properties (e.g., visual attributes; we know bananas are yellow) and knowledge of nonphysical properties (e.g., functional attributes; we know bananas are eatable). Miceli et al (2001) recently reported a brain-damaged patient (I.O.C.) who is severely impaired in accessing stored colour knowledge but shows no impairments for functional knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Naor-Raz et al, 2003) and for a colour versus semantic/functional distinction of stored knowledge (cf. Miceli et al, 2001). …”
Section: Colour-driven Eye Movementsmentioning
confidence: 99%
“…These high-level, cognitive aspects include elements of color knowledge (i.e., knowledge about prototypical object colors, Miceli et al, 2001) and perhaps the possibility of full conscious experience of color (Murphey et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Achromatopsia had thus to be distinguished from color agnosia (e.g. Beauvois and Saillant, 1985;Miceli et al, 2001). Patients with color agnosia can perform normally on these perceptual tests, but have impaired knowledge of colors.…”
Section: Introductionmentioning
confidence: 99%